Comparison of the Incidence of Postoperative Hypocalcemia following Total Thyroidectomy vs Completion Thyroidectomy. (30th October 2014) - Merchavy, Shlomo; Marom, Tal; Forest, Veronique‐Isabelle; Hier, Michael; Mlynarek, Alex; McHugh, Tobial; Payne, Richard
Abstract : Objective: To study the rate of postoperative hypocalcemia following completion thyroidectomy (CT), in comparison with the hypocalcemia rate following total thyroidectomy (TT). Study Design and Setting: A retrospective study, performed at the McGill University Thyroid Cancer Center, Montreal, Quebec, Canada, from 2007 to 2012. Subjects and Methods: Medical records of adult patients undergoing CT and TT operated by a single surgeon were reviewed. Data were extracted for demographics, postoperative calcium levels, surgical logs, and final surgical pathology. Hypocalcemia was defined as corrected serum calcium level ≤1.90 mmol/L, with concurrent serum parathyroid hormone <8 ng/L, and/or any signs or symptoms of hypocalcemia. Results: There were 68 CTs and 146 TTs. Transient hypocalcemia occurred in 1 of 68 (1.5%) and 18 of 146 (12.5%) patients in the CT and TT groups, respectively. The rate of hypocalcemia was significantly lower in the CT compared with the TT group ( P =. 02). In both groups, there were no cases of permanent hypocalcemia. Conclusion: The risk of transient of hypocalcemia in patients undergoing CT is significantly lower than the rate of hypocalcemia in patients undergoing TT.